Development in culture, ecophysiology and nutritional content of three South African Porphyra (Rhodophyta, Bangiales) species - Dlaza, Thembinkosi Steven (Department of Biological Sciences, 2014)
The first aim of this study was therefore to study the reproductive biology and phenology of three common Porphyra species (Porphyra aeodis Griffin, Bolton et Anderson 1999, Porphyra capensis Katzing 1843 and Porphyra saldanhae Stegenga, Bolton et Anderson 1997), which occur on the west coast of South Africa. The second aim of the study was to investigate, in culture, the ecophysiological responses of the different phases of the life histories of these threes species to various environmental variables. The third aim of this study was to quantify some important aspects of the nutritional composition of these three species and to investigate seasonal variations in these nutrients.